Time, space, and things - Ridley, B. K. (Cambridge : New York : Cambridge University Press, 1995)
"There are some wonderfully bizarre ideas in physics, and it seems a pity to keep them locked up in small boxes, available only to an esoteric coterie of key holders. Brian Ridley's book sets out to survey in simple, non-mathematical terms what physics has to say about the fundamental structure of the universe. He deals with all the basic concepts of modern physics: elementary particles, black holes, gravity, quantum theory, time, mass, relativity and energy; this new edition also includes coverage of more recently emerging ideas including strings, imaginary time and chaos. Ridley's clear and witty account gives an exciting introduction to the non-specialist while offering a fresh perspective to scientists themselves."--Jacket.
Includes index.
Keywords: Physics -- Popular works